Perovskite solar cell, preparation method thereof and photovoltaic module
By combining self-assembled single-molecule materials with pyrrolidone compounds, the homo energy level is reduced, and the problem of anti-solvent use in the preparation of traditional perovskite solar cell thin films is solved, and the preparation of high-performance anti-solvent-free perovskite solar cells is realized. Improved device performance and film quality.
Patent Information
- Application Number
- CN202411184521.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-08-27
AI Technical Summary
The preparation of traditional perovskite solar cell thin films requires anti-solvents, which limits the preparation size and toxicity problems, and hinders its large-scale application.
Self-assembled single-molecule materials are mixed with pyrrolidone compounds, and the homo energy level is reduced by combining carbonyl groups, and the reaction-free solvent perovskite solar cells are prepared to achieve adjustable hole transport layer energy level and improve film quality and device performance.
The preparation of high-performance anti-solvent-free perovskite solar cells is realized, which improves device performance and film quality, avoids the use of anti-solvents, and solves the problems of toxicity and preparation size limitations.
Smart Images

Figure CN119173110A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photovoltaic cells, and in particular to a perovskite solar cell and a preparation method thereof, and a photovoltaic module. Background Art
[0002] Perovskite solar cells are an important breakthrough in the field of photovoltaic technology in recent years. Perovskite materials have unique optoelectronic properties, including high absorption coefficient, long carrier diffusion length and tunable band gap, making them potential solar cell materials with high energy conversion efficiency. Since the first report of perovskite solar cells in 2009, their energy conversion efficiency has rapidly increased from the initial 3.8% to the current over 26%, close to the efficiency of silicon-based solar cells. This significant efficiency improvement is mainly attributed to material optimization, process improvement and device structure innovation. The general formula of perovskite materials is ABX3, where A is an organic or inorganic cation (such as methylammonium, ammonium methylammonium or cesium ion), B is a metal cation (such as lead or tin), and X is a halogen anion (such as iodine, bromine or chlorine). The unique crystal structure and chemical composition of perovskite enable it to effectively absorb sunlight and generate photogenerated charges, thereby improving the conversion efficiency of solar cells.
[0003] The main reason hindering the large-scale application of perovskite solar cells is the limitation of the perovskite film preparation process. The preparation of traditional perovskite films requires further treatment with anti-solvents to obtain perovskite films with better uniformity. However, the use of anti-solvents not only limits the preparation size of perovskites, but the toxicity of anti-solvents is also one of the main reasons.
[0004] Therefore, it is urgent to develop a method for preparing anti-solvent-free perovskite solar cells. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the first aspect of the present invention provides a method for preparing a perovskite solar cell; the method can avoid the use of an anti-solvent on the one hand, and can effectively improve the film quality and device performance on the other hand.
[0006] The second aspect of the present invention also provides a perovskite solar cell.
[0007] The third aspect of the present invention also provides a photovoltaic module.
[0008] A method for preparing a perovskite solar cell according to an embodiment of the first aspect of the present invention comprises the following steps:
[0009] S1, mixing a self-assembled monomolecular material (SAM) and an organic solvent to obtain a solution I; mixing the solution I and a pyrrolidone compound to obtain a solution II; coating the solution II on the surface of a conductive substrate; annealing I to obtain a hole transport layer;
[0010] S2, coating the perovskite precursor solution on the surface of the hole transport layer and performing annealing II to obtain a perovskite film;
[0011] S3, sequentially preparing an electron transport layer, a hole blocking layer and an electrode on the surface of the perovskite film to obtain a perovskite solar cell;
[0012] The pyrrolidone compound is selected from at least one of 2-pyrrolidone, N-methylpyrrolidone or N-ethylpyrrolidone.
[0013] The preparation method according to the embodiment of the present invention has at least the following beneficial effects:
[0014] In the related technology, self-assembled monomolecular materials are directly used as hole transport layers to prepare anti-solvent-free perovskite solar cells. However, since the homo energy level of the self-assembled monomolecular materials does not match the homo energy level of the anti-solvent-free perovskite film, hole transport is hindered and the opening voltage loss is large.
[0015] The present invention uses pyrrolidone compounds and self-assembled monomolecular materials for mixing; the carbonyl group on the pyrrolidone compounds is combined with the self-assembled monomolecular materials to achieve the purpose of lowering the homo energy level, thereby achieving adjustable energy levels of the hole transport layer, thereby preparing a high-performance antisolvent-free perovskite solar cell.
[0016] According to some embodiments of the present invention, the volume ratio of the solution I to the pyrrolidone compound is 100:(0.5-3). When the volume dosage of the pyrrolidone compound is too low, the improvement effect is not obvious. When the volume dosage of the pyrrolidone compound is too high, it will affect the agglomeration of SAM, thereby reducing the conductivity and hole transfer ability. Therefore, when the volume ratio of the solution I to the pyrrolidone compound is within the specified range of the present invention, high-performance perovskite solar cells can be prepared.
[0017] According to some embodiments of the present invention, the mass concentration of the solution I is 0.3 mg / mL to 1 mg / mL.
[0018] According to some embodiments of the present invention, the self-assembled monomolecular material is selected from at least one of ME-4PACZ ((4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid), MEO-2PACZ ((2-(3,6-dimethyl-9H-carbazole-9-yl)ethyl)phosphonic acid) or 4PADCB ([4-(7H-dibenzocarbazole-7-yl)butyl]phosphonic acid).
[0019] According to some embodiments of the present invention, the components of the perovskite precursor solution are selected from FA x Cs (1-x) PbI3; wherein x is 0.83 to 0.95. As a result, the crystal structure of the perovskite is more stable.
[0020] According to some embodiments of the present invention, in step S1, the temperature of annealing I is 80°C to 100°C.
[0021] According to some embodiments of the present invention, in step S1, the annealing I is performed for a period of 10 min to 30 min.
[0022] According to some embodiments of the present invention, in step S2, the temperature of annealing II is 130°C to 150°C.
[0023] According to some embodiments of the present invention, in step S2, the annealing II is performed for a period of 10 min to 30 min.
[0024] According to some embodiments of the present invention, the material of the electron transport layer is selected from C60 or PCBM.
[0025] According to some embodiments of the present invention, the material of the hole blocking layer is selected from at least one of BCP, acetylacetonate, and TPBi:1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene.
[0026] According to some embodiments of the present invention, the material of the electrode is selected from gold, copper or silver.
[0027] According to some embodiments of the present invention, the thickness of the electron transport layer is 30-50 nm.
[0028] According to some embodiments of the present invention, the barrier layer has a thickness of 6-10 nm.
[0029] According to some embodiments of the present invention, the thickness of the electrode is 100-200 nm.
[0030] According to some embodiments of the present invention, the conductive substrate includes an indium tin oxide conductive glass substrate (ITO) or a fluorine-doped tin dioxide conductive glass substrate (FTO).
[0031] According to some embodiments of the present invention, the conductive substrate is pre-treated before use.
[0032] According to some embodiments of the present invention, the pretreatment step includes cleaning, ultrasound and ultraviolet ozone irradiation.
[0033] A perovskite solar cell provided in an embodiment according to the second aspect of the present invention is prepared by the preparation method described in the first aspect of the present invention.
[0034] A third aspect of the present invention provides a photovoltaic module, comprising the perovskite solar cell described in the second aspect of the present invention.
[0035] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0037] Figure 1 3 is a JV curve diagram of the perovskite solar cells prepared in the embodiments of the present invention and the comparative examples.
[0038] Figure 2 It is an infrared spectrum of the self-assembled monomolecular material of an embodiment of the present invention. DETAILED DESCRIPTION
[0039] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.
[0040] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0041] Example 1
[0042] This example provides a perovskite solar cell, and the preparation method thereof is as follows:
[0043] Conductive glass substrate pretreatment: (1) using a conductive glass cleaning agent, deionized water, and ethanol to clean the ITO conductive glass substrate, and performing ultrasound at 99% power for 30 minutes to obtain a clean ITO conductive glass substrate;
[0044] (2) Take a clean ITO conductive glass substrate and expose it to UV-ozone cleaning for 30 minutes.
[0045] Perovskite precursor solution: Take 461 mg PbI2, 142.8 mg FAI, 27.8 mg PbCl2, and 44.2 mg CsI2 and stir them by vibration in a mixed solution of DMF:NMP=500:96, stir for 2 hours, and let it stand to obtain a uniform perovskite precursor solution.
[0046] S1. Take 0.3 mg of ME-4PACZ and stir it in 1 mL of isopropanol solution by vibration, stir for 30 min, and let it stand to obtain a uniform SAM molecular solution I; take 10 μL of 2-pyrrolidone and add it to the SAM molecular solution I, and continue stirring for 30 min to obtain solution II;
[0047] Solution II was spin-coated on an ITO conductive substrate to prepare a monolayer film at a speed of 4000 rpm for 30 s, followed by annealing on a heating platform at 100° C. for 10 min to obtain a hole transport layer.
[0048] S2, taking the perovskite precursor solution, using the spin coating method to perform anti-solvent-free preparation on the hole transport layer, the spin coating speed is 5000 rpm, the spin coating time is 50 s, and then annealing at 150 ° C for 10 min to obtain an anti-solvent-free perovskite film;
[0049] S3. Place the perovskite film in a vacuum evaporation chamber, and sequentially evaporate C60 with a thickness of 40 nm, BCP with a thickness of 8 nm, and Cu with a thickness of 100 nm; thus, a solar perovskite cell is obtained.
[0050] Example 2
[0051] This example provides a perovskite solar cell, and the preparation method thereof is as follows:
[0052] Conductive glass substrate pretreatment: (1) using a conductive glass cleaning agent, deionized water, and ethanol to clean the ITO conductive glass substrate, and performing ultrasound at 99% power for 30 minutes to obtain a clean ITO conductive glass substrate;
[0053] (2) Take a clean ITO conductive glass substrate and expose it to light in a UV-ozone cleaning machine for 30 minutes.
[0054] Perovskite precursor solution: Take 461 mg PbI2, 142.8 mg FAI, 27.8 mg PbCl2, and 44.2 mg CsI2 and stir them by vibration in a mixed solution of DMF:NMP=500:96, stir for 2 hours, and let it stand to obtain a uniform perovskite precursor solution.
[0055] S1. Take 0.3 mg of ME-4PACZ and stir it in 1 mL of isopropanol solution by vibration, stir for 30 min, and let it stand to obtain a uniform SAM molecular solution I; take 10 μL of N-methylpyrrolidone and add it to the SAM molecular solution I, and continue stirring for 30 min to obtain solution II;
[0056] Solution II was spin-coated on an ITO conductive substrate to prepare a monolayer film at a speed of 4000 rpm for 30 s, followed by annealing on a heating platform at 100° C. for 10 min to obtain a hole transport layer.
[0057] S2, taking the perovskite precursor solution, using the spin coating method to perform anti-solvent-free preparation on the hole transport layer, the spin coating speed is 5000 rpm, the spin coating time is 50 s, and then annealing at 150 ° C for 10 min to obtain an anti-solvent-free perovskite film;
[0058] S3. Place the perovskite film in a vacuum evaporation chamber, and sequentially evaporate C60 with a thickness of 40 nm, BCP with a thickness of 8 nm, and Cu with a thickness of 100 nm; thus, a solar perovskite cell is obtained.
[0059] Example 3
[0060] This example provides a perovskite solar cell, and the preparation method thereof is as follows:
[0061] Conductive glass substrate pretreatment: (1) using a conductive glass cleaning agent, deionized water, and ethanol to clean the ITO conductive glass substrate, and performing ultrasound at 99% power for 30 minutes to obtain a clean ITO conductive glass substrate;
[0062] (2) Take a clean ITO conductive glass substrate and expose it to light in a UV-ozone cleaning machine for 30 minutes.
[0063] Perovskite precursor solution: Take 461 mg PbI2, 142.8 mg FAI, 27.8 mg PbCl2, and 44.2 mg CsI2 and stir them by vibration in a mixed solution of DMF:NMP=500:96, stir for 2 hours, and let it stand to obtain a uniform perovskite precursor solution.
[0064] S1. Take 0.3 mg of ME-4PACZ and stir it in 1 mL of isopropanol solution by vibration, stir for 30 min, and let it stand to obtain a uniform SAM molecular solution I; take 10 μL of N-ethylpyrrolidone and add it to the SAM molecular solution I, and continue stirring for 30 min to obtain solution II;
[0065] Solution II was spin-coated on an ITO conductive substrate to prepare a monolayer film at a speed of 4000 rpm for 30 s, followed by annealing on a heating platform at 100° C. for 10 min to obtain a hole transport layer.
[0066] S2, taking the perovskite precursor solution, using the spin coating method to perform anti-solvent-free preparation on the hole transport layer, the spin coating speed is 5000 rpm, the spin coating time is 50 s, and then annealing at 150 ° C for 10 min to obtain an anti-solvent-free perovskite film;
[0067] S3. Place the perovskite film in a vacuum evaporation chamber, and sequentially evaporate C60 with a thickness of 40 nm, BCP with a thickness of 8 nm, and Cu with a thickness of 100 nm; thus, a solar perovskite cell is obtained.
[0068] Example 4
[0069] This example provides a perovskite solar cell, and its preparation method is basically the same as that of Example 1, except that the volume ratio of solution I to the pyrrolidone compound is 100:3.
[0070] Example 5
[0071] This example provides a perovskite solar cell, and its preparation method is basically the same as that of Example 1, except that the volume ratio of solution I to the pyrrolidone compound is 100:0.5.
[0072] Example 6
[0073] This example provides a perovskite solar cell, and its preparation method is basically the same as that of Example 1, except that the volume ratio of solution I to the pyrrolidone compound is 100:5.
[0074] Example 7
[0075] This example provides a perovskite solar cell, and its preparation method is basically the same as that of Example 1, except that the volume ratio of solution I to the pyrrolidone compound is 100:0.1.
[0076] Comparative Example 1
[0077] Comparative Example 1 provides a perovskite solar cell, and the preparation method thereof is as follows:
[0078] Conductive glass substrate pretreatment: (1) using a conductive glass cleaning agent, deionized water, and ethanol to clean the ITO conductive glass substrate, and performing ultrasound at 99% power for 30 minutes to obtain a clean ITO conductive glass substrate;
[0079] (2) Take a clean ITO conductive glass substrate and expose it to light in a UV-ozone cleaning machine for 30 minutes.
[0080] Perovskite precursor solution: Take 461 mg PbI2, 142.8 mg FAI, 27.8 mg PbCl2, and 44.2 mg CsI2 and stir them by vibration in a mixed solution of DMF:NMP=500:96, stir for 2 hours, and let it stand to obtain a uniform perovskite precursor solution.
[0081] S1. Take 0.3 mg of ME-4PACZ and stir it in 1 mL of isopropanol solution by vibration, stir for 30 min, and let it stand to obtain a uniform SAM molecular solution I;
[0082] The SAM molecular solution I was spin-coated on an ITO conductive substrate to prepare a monomolecular film at a spin coating speed of 4000 rpm for 30 s, and then annealed on a heating table at 100° C. for 10 min to obtain a hole transport layer.
[0083] S2, taking the perovskite precursor solution, using the spin coating method to perform anti-solvent-free preparation on the hole transport layer, the spin coating speed is 5000 rpm, the spin coating time is 50 s, and then annealing at 150 ° C for 10 min to obtain an anti-solvent-free perovskite film;
[0084] S3. Place the perovskite film in a vacuum evaporation chamber, and sequentially evaporate C60 with a thickness of 40 nm, BCP with a thickness of 8 nm, and Cu with a thickness of 100 nm; thus, a solar perovskite cell is obtained.
[0085] Comparative Example 2
[0086] Comparative Example 2 provides a perovskite solar cell, and its preparation method is as follows:
[0087] Conductive glass substrate pretreatment: (1) using a conductive glass cleaning agent, deionized water, and ethanol to clean the ITO conductive glass substrate, and performing ultrasound at 99% power for 30 minutes to obtain a clean ITO conductive glass substrate;
[0088] (2) Take a clean ITO conductive glass substrate and expose it to UV-ozone cleaning for 30 minutes.
[0089] Perovskite precursor materials 462mgPbI2, 142.8mgFAI, 27.8mgPbCl2, 44.2mgCsI2 were mixed with 500mL precursor solvent IDMF, 96uL precursor solvent IINMP, and 0.5mg single molecule self-assembly material ME-4PACZ, and the perovskite precursor solution was obtained after vibrating and stirring for 2h;
[0090] The precursor solution was taken and anti-solvent-free preparation was performed on the conductive glass substrate ITO by spin coating, the spin coating speed was 5000 rpm, the spin coating time was 50 s, and then annealed at 150 ° C for 10 min to obtain an anti-solvent-free perovskite film;
[0091] The perovskite film was placed in a vacuum evaporation chamber, and C60 with a thickness of 40 nm, BCP with a thickness of 8 nm, and Cu with a thickness of 100 nm were sequentially evaporated to obtain a solar cell.
[0092] Performance Testing
[0093] The solution II prepared in step S1 of Examples 1 to 3 of the present invention and the SAM molecule solution I in Comparative Example 1 were subjected to infrared testing, and the results are as follows: Figure 2 As shown, the peak positions of the transmittance at the yellow line position in the figure are shifted to a certain extent between Comparative Example 1 and Examples 1, 2, and 3, indicating that the pyrrolidone additives interact with each other after being added to the SAM solution.
[0094] The perovskite solar cells prepared in Examples 1 to 7 of the present invention and Comparative Example 1 were subjected to JV tests. The results of Examples 1 to 3 and Comparative Example 1 are as follows: Figure 1 The data are shown in Table 1.
[0095] Table 1 Examples 1 to 7 and Comparative Examples 1 to 2
[0096]
[0097] From the data in Table 1, it can be seen that the perovskite solar cells prepared in Examples 1 to 3 of the present invention have higher open circuit voltage, photoelectric conversion efficiency, fill factor and short circuit current than the perovskite solar cell in Comparative Example 1, which indicates that the present invention adopts a mixture of pyrrolidone compounds and self-assembled monomolecular materials; the carbonyl group on the pyrrolidone compound is combined with the self-assembled monomolecular material to achieve the purpose of lowering the HOMO energy level, thereby achieving adjustable energy level of the hole transport layer; thereby preparing a high-performance anti-solvent-free perovskite solar cell.
[0098] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A method for preparing a perovskite solar cell, characterized in that: The steps include: S1, mixing a self-assembled monomolecular material and an organic solvent to obtain a solution I; mixing the solution I and a pyrrolidone compound to obtain a solution II; coating the solution II on the surface of a conductive substrate; annealing I to obtain a hole transport layer; S2, coating the perovskite precursor solution on the surface of the hole transport layer and performing annealing II to obtain a perovskite film; S3, sequentially preparing an electron transport layer, a hole blocking layer and an electrode on the surface of the perovskite film to obtain a perovskite solar cell; The pyrrolidone compound is selected from at least one of 2-pyrrolidone, N-methylpyrrolidone or N-ethylpyrrolidone.
2. The method for preparing a perovskite solar cell according to claim 1, characterized in that: The volume ratio of the solution I to the pyrrolidone compound is 100:(0.5-3).
3. The method for preparing a perovskite solar cell according to claim 1, characterized in that: The mass concentration of the solution I is 0.3 mg / mL to 1 mg / mL.
4. The method for preparing a perovskite solar cell according to claim 1, characterized in that: The self-assembled monomolecular material is selected from at least one of ME-4PACZ, MEO-2PACZ or 4PADCB.
5. The method for preparing a perovskite solar cell according to claim 1, characterized in that: The components of the perovskite precursor solution are selected from FA x Cs (1-x) PbI3; wherein x is 0.83 to 0.
95.
6. The method for preparing a perovskite solar cell according to claim 1, characterized in that: In step S1, the temperature of the annealing I is 80°C to 100°C.
7. The method for preparing a perovskite solar cell according to claim 1, characterized in that: In step S2, the temperature of annealing II is 130°C to 150°C.
8. The method for preparing a perovskite solar cell according to claim 1, characterized in that: In step S2, the annealing II is performed for 10 to 30 minutes.
9. A perovskite solar cell, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.
10. A photovoltaic module, characterized in that: Includes the perovskite solar cell as described in claim 9.
Citation Information
Patent Citations
Preparation method and application of self-assembled monomolecular layer, perovskite solar cell and preparation method of perovskite solar cell
CN117998941A
